Synthesis and crystal structure of poly[aqua(μ4-(1R,2S,4R)-4-hydroxy-1-((7-hydroxy-3-(4-hydroxy-3-sulfonatophenyl)-4-oxo-4H-chromen-8-yl)methyl)pyrrolidin-1-ium-2-carboxylate-κ4O:O′:O″:O‴)sodium(I)] monohydrate, C21H22NNaO12S - Chen Hai-Lin; Huang Xiu-Xiang; Lan Jian-Jing; Yao Dong-Mei; Wang Yan-Ping; Liu Qiu-Ping (Zeitschrift für Kristallographie - New Crystal Structures)
C21H22NNaO12S, orthorhombic, P212121 (no. 19), a = 7.6850(1) Å, b = 10.8030(1) Å, c = 25.9262(2) Å, V = 2152.42(4) Å3, Z = 4, Rgt(F) = 0.0309, wRref(F2) = 0.0818, T = 100.0(4) K.